Experiment unlearned: Unpacking leadership and learning of key actors in a Hong Kong street experiment - Kristen J. Zhao; Robin A. Chang; Guibo Sun (Journal of Urban Mobility)
Street experiments are implemented worldwide, yet they have not achieved notable transformative change in Hong Kong despite numerous initiatives. This study explores the reasons for their limited impact through a case study of the Healthy Street Lab 2.0, a street experiment organised by a civil society group. This initiative involved collaboration between the government and civil society, using a co-creative design approach. Although well-resourced, the experiment did not achieve its goals, with most design prototypes eventually discontinued. Through interviews and surveys, we collected insights from key stakeholders (n = 13) regarding their motivations, challenges, and reflections and participants for their feedback (n = 14). Our analysis reveals how the dynamics of low willingness to learn and the capacity to lead among key actors led to a reduced vision, scope, and design, ultimately missing initial objectives. We underscore the role of power differentials and institutional barriers in this process. We conclude by offering reflection points for stakeholders to consider in future experiments. This study contributes to understanding learning and leadership dynamics in the evolving literature on the transformative potential of street experiments.